2014
DOI: 10.1097/shk.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Inflammatory Response and Reduction in Infarct Size by Postconditioning Are Associated With Downregulation of Early Growth Response 1 During Reperfusion in Rat Heart

Abstract: Early growth response 1 (EGR-1) works as a master regulator that plays a key role in triggering inflammation-induced tissue injury after ischemia and reperfusion. This study tested the hypothesis that postconditioning (Postcon) or anti-inflammatory compound, curcumin, ameliorates inflammatory responses and further reduces infarct size by normalizing EGR-1 expression during reperfusion. In the control group, male Sprague-Dawley rats were subjected to 30-min ischemia and 180-min reperfusion. Postcon with four cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…Fiber and acetate improved heart and kidney function through regulation of key pathways and genes involved in cardiovascular health, including the transcription factor Egr1, a master regulator of CVD through cardiac and renal fibrosis, inflammation, and cardiac hypertrophy. [29][30][31] Fiber also downregulated the proinflammatory IL-1 cytokine signaling in the kidney. This is consistent with our fundamental hypothesis, which was based on the recent demonstration of a strong link between dietary fiber, the gut microbiota, and the pathogenesis of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Fiber and acetate improved heart and kidney function through regulation of key pathways and genes involved in cardiovascular health, including the transcription factor Egr1, a master regulator of CVD through cardiac and renal fibrosis, inflammation, and cardiac hypertrophy. [29][30][31] Fiber also downregulated the proinflammatory IL-1 cytokine signaling in the kidney. This is consistent with our fundamental hypothesis, which was based on the recent demonstration of a strong link between dietary fiber, the gut microbiota, and the pathogenesis of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 93%
“…29 Particularly relevant to the present study is the role of Egr1 in cardiac hypertrophy, renal fibrosis, and inflammation. [29][30][31] A diet rich in fiber is associated with the production of substantial quantities of SCFAs such as acetate. 10 SCFAs are thought to act in the gut via metabolite-sensing receptors such as the inhibitory G-protein coupled receptor GPR43, which interacts with acetate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Revascularization could improve the prognosis of the patients with acute myocardial infarction (1), however, reperfusion could induce additional injury, which is sometimes extremely severe or fatal and diminishes the benefits of revascularization. Basic studies (3)(4)(5)(6) and small-sample clinical data (7,8) have verified that ischemic postconditioning (IPOC) could attenuate injury induced by ischemia/reperfusion (IR) and certain studies (8)(9)(10) have indicated that the mitochondrial K ATP (mitoK ATP ) channel plays an important role in cardioprotection effects of IPOC, but its molecular mechanisms are not completely clear thus far. Connexin 43 (Cx43; a gap junction protein located mainly in the ventricular myocardium in mammals) plays an important role in intercellular electrical conduction and cell survival, but whether the changes of membrane Cx43 are involved in IPOC-induced cardioprotective effects and the corresponding details is unclear.…”
Section: Introductionmentioning
confidence: 99%